Association of methylenetetrahydrofolate reductase (MTHFR) rs1801133 (677C>T) gene polymorphism with ischemic stroke risk in different populations: An updated meta-analysis - Zhao, Lili; Li, Tao; Dang, Meijuan; Li, Ye; Fan, Hong; Hao, Qian; Song, Dingli; Lu, Jialiang; Lu, Ziwei; Jian, Yating; Wang, Heying; Wang, Xiaoya; et al. (Frontiers in Genetics, 2023)
Background: Recently, increasing evidence has implicated methylenetetrahydrofolate reductase (MTHFR) gene mutation as a risk factor for ischemic stroke (IS) in the general population. However, studies have been inconclusive and lack evidence on specific populations. We aim to determine whether the rs1801133 (NC_000001.11 (MTHFR):g. 677C>T (p.Ala222Val) variant, we termed as MTHFR rs1801133 (677 C>T), is linked to an increased risk of IS in different age groups and ancestry groups. Methods: The literature relevant to our study was found by searching the PubMed, Cochrane Library, Web of Science, EMBASE, and CNKI databases. A random effect model analysis was used to calculate the pooled odds ratio (OR) and 95% confidence interval (CI) to evaluate any possible association. We conducted a subgroup analysis based on the age and ancestry groups of the included populations. Results: As of March 2022, 1,925 citations had been identified in electronic databases, of which 96 studies involving 34,814 subjects met our eligibility criteria. A strong link was found between IS and the MTHFR gene rs1801133 (677C>T) polymorphism in all genetic models [dominant genetic model (OR = 1.47; 95%CI = 1.33–1.61; p < 0.001), recessive genetic model (OR = 1.52; 95%CI = 1.36–1.71; p < 0.001), heterozygous model (OR = 1.36; 95%CI = 1.24–1.48; p < 0.001), homozygous model (OR = 1.82; 95%CI = 1.58–2.11; p < 0.001), and T allelic genetic model (OR = 1.37; 95%CI = 1.27–1.48; p < 0.001)]. Further subgroup analyses indicated that the MTHFR rs1801133 (677C>T) variant may increase the risk of IS in Asian, Hispanic, or Latin population, middle-aged, and elderly populations (p < 0.001). Conclusion: Our results implied that mutation of the T allele of MTHFR rs1801133 (677C>T) could be a risk factor for IS. A significant association was found among Asian, Hispanic, or Latin population, middle-aged, and elderly people.